Pemanfaatan Platform SDi (SEKOLAH DIGITAL) dalam Mendukung Tranformasi Pendidikan di Sekolah Dasar - Azzah Arifina, Lutfi; Suriansyah, Ahmad; Harsono, Arta Mulya Budi (LPPM Universitas PGRI Argopuro Jember, 2026)
ABSTRACT: The SDi Platform is a digital platform recommended by the Department of Education with the aim of supporting educational transformation to meet the demands of the Society 5.0 era. The utilization of the SDi platform is integrated into daily school activities as a means of fostering students’ technological adaptation at the elementary school level. This study aims to examine how the implementation of the SDi platform supports educational transformation at SDN Pasar Lama 3 Banjarmasin. The research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, involving the school operator, principal, two teachers, and one student. The findings indicate that the SDi platform has a positive impact on educational activities in elementary schools; however, the implementation process also faces several challenges. The study further provides appropriate solutions, including comprehensive training programs, upgrading of school infrastructure, and the development of innovative platform features to enhance the effectiveness of digital education transformation.